ELEMENTS OF PROVINCIAL AUTONOMY: THE RIGHT TO REGULATE AUTHORITIES, FINANCE, ACTS AND PROTECTION: 1. УВОД 2. ПРАВО НА САМОСТАЛНО УРЕЂИВАЊЕ ОРГАНА ВЛАСТИ 3. ФИНАНСИЈСКА АУТОНОМИЈА ПОКРАЈИНÂ 4. ПРАВНИ АКТИ АУТОНОМНЕ ПОКРАЈИНЕ 5. ЗАШТИТА ПОКРАЈИНСКЕ АУТОНОМИЈЕ 6. ЗАКЉУЧАК - Orlović, Slobodan Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Summary: the paper critically analyzes some of the elements of provincial autonomy contained in the Constitution of Serbia. Creating the autonomy, some of those segments of autonomy are an expression of the pure self-government of the autonomous province (original affairs), while others segments represent rights that are confirmed and regulated by state’s law, and we cannot name them as original. The right to self-regulation of authorities and the right to protection of province, as elements of autonomy, belong to the first group, while provincial finances and acts (regulations) must be regulated in accordance with the law.